Nature-based solutions to climate change adaptation in urban areas : linkages between science, policy and practice - Kabisch, Nadja; Korn, Horst; Stadler, Jutta; Bonn, Aletta (SpringerOpen, 2017)
This book is open access under a CC BY 4.0 license. This book brings together research findings and experiences from science, policy and practice to highlight and debate the importance of nature-based solutions to climate change adaptation in urban areas. Emphasis is given to the potential of nature-based approaches to create multiple-benefits for society. The expert contributions present recommendations for creating synergies between ongoing policy processes, scientific programmes and practical implementation of climate change and nature conservation measures in global urban areas.
Includes index.
Keywords: City planning -- Climatic factors.; City planning -- Environmental aspects.; Climate change mitigation.; Sustainable development.; elektronické knihy; electronic books